Modeling critical thinking in information seeking process of postgraduate students / Mahboobeh Haghparast - Mahboobeh , Haghparast (2017)
Critical thinking is an important outcome of higher education in the 21st century. However, there are several reports about the lack of critical thinking skills among students in workplaces and industries. Critical thinking helps students to seek information better than persons who cannot think critically. This study examines critical thinking skills among postgraduates and investigates its relationship with information seeking processes. Therefore, the following objectives were put forward: i) to investigate the association between critical thinking skills and information seeking process; ii) to design and develop a prototype, namely “Learning System for Critical Thinking in Information Seeking” (LeCTIS) to encourage critical thinking skills in information seeking process; iii) to evaluate the usability and functionality of the LeCTIS prototype in facilitating critical thinking in the information seeking process. Quantitative research approach is employed in this research using survey and interview. The sample population was derived from postgraduates in University of Malaya. The survey was conducted to examine the level of critical thinking among postgraduates and to investigate the relationship between critical thinking skills and information seeking processes using RED model and WGCTA-UK edition and the Information Seeking Process (ISP) model. The interviews were conducted to grab deep information on how postgraduates assess the information they received, the user’s requirements, and the influenced factors on critical thinking skills. The development of the LeCTIS prototype was conducted using the results of the analysis of the interviews and surveys, which revealed the association between critical thinking skills and information seeking processes. To analyze the survey, descriptive and inferential statistics were used and selective, open, and axial coding was used to analyze the interview. The survey and interview findings provided the requirements, which determined the design consideration for the LeCTIS prototype development. The findings from the survey and interview indicated that there was an association between critical thinking skills and information seeking processes among respondents at a different level. Therefore, the development of the LeCTIS helps students learn to use critical thinking skills while seeking for information. The LeCTIS prototype was evaluated using Software Usability Measurement Inventory (SUMI) as well as pre-test post-test experiment. The results indicated a positive feedback on its usability and functionality. This study is significant for higher learning institutes, instructors, and education system with the aim of training qualified students in critical thinking skills.